Molecular Strategies for Intensity-Dependent Olfactory Processing in Caenorhabditis elegans - Cheng, Hankui; Liu, Yu; Xue, Yadan; Shao, Jiajie; Tan, Zhibing; Liu, Siyan; Duan, Shumin; Kang, Lijun (Frontiers in Molecular Neuroscience, 2021)
Various odorants trigger complex animal behaviors across species in both quality- and quantity-dependent manners. However, how the intensity of olfactory input is encoded remains largely unknown. Here we report that isoamyl alcohol (IAA) induces bi-directional currents through a Gα- guanylate cyclase (GC)- cGMP signaling pathway in Caenorhabditis elegans olfactory neuron amphid wing “C” cell (AWC), while two opposite cGMP signaling pathways are responsible for odor-sensing in olfactory neuron amphid wing “B” cell (AWB): (1) a depolarizing Gα (GPA-3)- phosphodiesterase (PDE) – cGMP pathway which can be activated by low concentrations of isoamyl alcohol (IAA), and (2) a hyperpolarizing Gα (ODR-3)- GC- cGMP pathway sensing high concentrations of IAA. Besides, IAA induces Gα (ODR-3)-TRPV(OSM-9)-dependent currents in amphid wing “A” cell (AWA) and amphid neuron “H” cell with single ciliated sensory ending (ASH) neurons with different thresholds. Our results demonstrate that an elaborate combination of multiple signaling machineries encode the intensity of olfactory input, shedding light on understanding the molecular strategies on sensory transduction.